Retrospective evaluation of autotransfusion using a cell saver device versus allotransfusion in the perioperative management of acute hemoperitoneum in 43 dogs (2017–2021) - Blunschi, Fabienne; Gluding, Dennis; Hassdenteufel, Esther; Schneider, Matthias; Lehmann, Hendrik (Frontiers in Veterinary Science, 2025)
BackgroundCell saver (CS) technology is an increasingly popular approach for autotransfusion in small animal veterinary medicine for the treatment of patients with abdominal hemorrhagic effusion.ObjectiveTo evaluate the utility, effectiveness, and safety of autotransfusions collected with a CS device and to assess whether the use of the CS device reduces the demand for allogenic blood transfusions.Materials and methodsRetrospective study of dogs with acute hemoperitoneum of splenic origin treated surgically. Dogs were grouped by the type of transfusion received: allo- and autotransfusion (AA), allotransfusion only (AO), autotransfusion only (CS), and no transfusion (NT). Differences in changes of laboratory parameters (hematocrit and lactate), transfusion volume, and outcomes were analyzed across groups.ResultsForty-three dogs were included. Twenty-seven (62.8%) suffered from hemangiosarcoma, and 16 (37.2%) had a benign cause of hemoperitoneum. The classification into blood transfusion groups was as follows: 7/43 (16.3%) in the AA-group, 11/43 (25.6%) in the AO-group, 11/43 (25.6%) in the CS-group and 14/43 (32.6%) in the NT-group. Increase in hematocrit over time was similar in all subgroups that received any form of blood transfusion (AA-, AO-, CS-group). Total volume of transfused blood (autologous and allogenic) was significantly higher in the AA-group (median 54.0mL/kg, range 24.7–126.5mL/kg) than in the AO-group (median 7.6mL/kg, range 4.6–13.5mL/kg, p = 0.01) but not the CS-group (median 23.8mL/kg, range 14.1–50.0mL/kg, p = 0.22). No difference was found for the volume of allogenic blood transfused between the AA-group (median 9.4mL/kg, range 5.0–16.2mL/kg) and AO-group (median 7.6mL/kg, range 4.6–13.5mL/kg) (p = 0.68). The use of the CS device did not adversely affect the time from presentation to surgery, the duration of surgery, or the outcomes.DiscussionThe use of autologous blood transfusions obtained by CS device in dogs suffering from acute hemoperitoneum caused by a benign or malignant splenic disorder appeared safe and effective in the cases described. And therefore may emphasize its further application as an addition or alternative to traditional allogenic blood transfusions.